2010
DOI: 10.1159/000320158
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Analysis of the Microbiota of Severe Early Childhood Caries

Abstract: Background/Aims: Severe early childhood caries is a microbial infection that severely compromises the dentition of young children. The aim of this study was to characterize the microbiota of severe early childhood caries. Methods: Dental plaque samples from 2- to 6-year-old children were analyzed using 16S rRNA gene cloning and sequencing, and by specific PCR amplification for Streptococcus mutans and Bifidobacteriaceae species. Results: Children with severe caries (n = 39) had more dental plaque and gingival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
173
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(193 citation statements)
references
References 82 publications
8
173
1
2
Order By: Relevance
“…Mitis group streptococci are early colonizers of oral cavity surfaces and form the basis of many of the polymicrobial communities found in the mouth and nasopharynx (Aas et al, 2005;Kanasi et al, 2010;Shak et al, 2013;Xu et al, 2014a). Such communities may also contain C. albicans, which is carried by~40 % of the healthy adult population (Clayton & Noble, 1966), and it is suggested that synergistic interactions between C. albicans and streptococci can promote carriage as well as disease (Dutton et al, 2014;Falsetta et al, 2014;Xu et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Mitis group streptococci are early colonizers of oral cavity surfaces and form the basis of many of the polymicrobial communities found in the mouth and nasopharynx (Aas et al, 2005;Kanasi et al, 2010;Shak et al, 2013;Xu et al, 2014a). Such communities may also contain C. albicans, which is carried by~40 % of the healthy adult population (Clayton & Noble, 1966), and it is suggested that synergistic interactions between C. albicans and streptococci can promote carriage as well as disease (Dutton et al, 2014;Falsetta et al, 2014;Xu et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…The main habitats of oral Veillonella species are tongue biofilms, dental biofilms, buccal mucosa, and saliva (Hughes et al, 1988;Mashima et al, 2016;Liljemark and Gibbons, 1971). Oral Veillonella species, particularly V. parvula, have been detected in severe early childhood caries (Kanasi et al, 2010) and intraradicular infections (Sundqvist, 1992), including abscesses (Khamaleelakul et al, 2002), apical root canals (Baumgartner and Falkler Jr., 1991), and dental tubules (Peters et al, 2001). In addition, oral Veillonella species have been detected in saliva (Takeshita et al, 2009) and subgingival biofilm specimens (Heller et al, 2012;Mashima et al, 2015;Silva-Boghossian et al, 2013) from patients with chronic periodontitis.…”
Section: Issn: 2319-7706 Volume 6 Number 7 (2017) Pp 449-461mentioning
confidence: 99%
“…Among these, mutans streptococci are considered to be the primary pathogens of dental caries (Thenisch et al, 2006). However, due to the complex interspecies interactions, there is also evidence to suggest that other species of oral streptococci may have different roles in the caries process (Kanasi et al, 2010). Most previous studies on the microbial risk indicators for dental caries have focused mainly on one or several possible pathogens Ge et al, 2008;Okada et al, 2005).…”
Section: Oral Streptococci Succession Associated With S-eccmentioning
confidence: 99%
“…Initial attachment of oral streptococci determines the composition of later colonizers in the oral biofilm and impacts the caries status (Filoche et al, 2010). Although most investigations implicate mutans streptococci as the principal aetiological agents in early childhood caries, due to their prevalence in carious lesions (Thenisch et al, 2006), the mere presence of mutans streptococci is not sufficient to predict the formation of dental caries; other oral streptococcal species may also moderate caries outcome (Kanasi et al, 2010). To date, little is known about the changes in the diversity and composition of oral streptococci in relation to S-ECC.…”
Section: Introductionmentioning
confidence: 99%